The pen falls from the hand: recovery of the Memory of Malaga epidemics by the pharmacist Joaquín García Briz y Galindo - Barrena Gómez, Ana (Documenta & Instrumenta - Documenta et Instrumenta, 2022)
This article focuses on the study of the Memory of Malaga epidemics, a document drawn up in 1859 by the Malaga pharmacist Joaquín García Briz y Galindo to be sent to the Royal National Academy of Pharmacy, where it is currently kept. Through it, is intended to extract the author’s personal perspective on the different epidemic outbreaks of yellow fever and Asian morbid cholera that ravaged the country during this century. In addition, we will analyze the sources on which it´s based to recompose and carry out its mission, as well as his personal experiences, which will allow us to construct and sketch his biography.
Keywords: Memory of Malaga epidemics; Joaquín García Briz y Galindo; 19th century; epidemic diseases; history of health